CELEBRITY ENDORSER DAN BRAND IMAGE SEBAGAI DETERMINAN KEPUTUSAN PEMBELIAN PRODUK SCARLETT WHITENING DI SUMBAWA BESAR - I Nyoman Sutama; Sri Rahayu; Gusti Agung Try Widnyani (Samalewa: Jurnal Riset & Kajian Manajemen, 2023)
This study aims to know the effect of celebrity endorser and brand image on purchasing decisions of Scarlett Whitening in Sumbawa Besar. The type of this study was associative study. The type of data used is quantitative obtained from primary sources. Total of population in this study was 110. The sampling technique used a saturated sample, thus the number of samples in this study was 110 people. The method used to collect data is using a questionnaire. Data analysis was performed using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and coefficient of determination test (R2). The results of this study showed that the celebrity endorsers and brand image had a positive and significant effect on the purchasing decision of Scarlett Whitening in Sumbawa Besar, both partially and simultaneously. the percentage effect of celebrity endorsers and brand image on the purchasing decision of Scarlett Whitening in Sumbawa Besar is 50.7%, while the remaining 49.3% is influenced by other variables outside of this study, such as product factors and cultural factors. Product factors consist of psychological factors, social factors and business atmosphere factors, while cultural factors consist of cultural factors, price factors and promotion factors.